Effectiveness of experimental dentifrices based on essential oils on biofilm on complete dentures: an in vitro study - Andrezza Cristina Moura dos Santos; Filipe Santos Ferreira Mendes; Fernanda Thaís Pompeo; Evandro Watanabe; Ana Paula Macedo; Valéria Oliveira Pagnano de Souza; Helena de Freitas Oliveira Paranhos; Cláudia Helena Silva-Lovato (University of São Paulo, 2024)
Abstract Specific products containing natural resources can contribute to the innovation of complete denture hygiene. Objective: To conduct an in vitro evaluation of experimental dentifrices containing essential oils of Bowdichia virgilioides Kunth (BvK), Copaifera officinalis (Co), Eucalyptus citriodora (Ec), Melaleuca alternifolia (Ma) and Pinus strobus (Ps) at 1%. Methodology: The variables evaluated were organoleptic and physicochemical characteristics, abrasiveness (mechanical brushing machine) simulating 2.5 years, and microbial load (Colony Forming Units - CFU/mL), metabolic activity (XTT assay) and cell viability (Live/Dead® BacLight™ kit) of the multispecies biofilm (Streptococcus mutans: Sm, Staphylococcus aureus: Sa, Candida albicans: Ca and Candida glabrata: Cg). Specimens of heat-polymerized acrylic resins (n=256) (n=96 specimens for abrasiveness, n=72 for microbial load count, n=72 for biofilm metabolic activity, n=16 for cell viability and total biofilm quantification) with formed biofilm were divided into eight groups for manual brushing (20 seconds) with a dental brush and distilled water (NC: negative control), Trihydral (PC: positive control), placebo (Pl), BvK, Co, Ec, Ma or Ps. After brushing, the specimens were washed with PBS and immersed in Letheen Broth medium, and the suspension was sown in solid specific medium. The organoleptic characteristics were presented by descriptive analysis. The values of density, pH, consistency and viscosity were presented in a table. The data were analyzed with the Wald test in a generalized linear model, followed by the Kruskal-Wallis test, Dunn's test (mass change) and the Bonferroni test (UFC and XTT). The Wald test in Generalized Estimating Equations and the Bonferroni test were used to analyze cell viability. Results: All dentifrices showed stable organoleptic characteristics and adequate physicochemical properties. CN, Ec, Ps, Pl and PC showed low abrasiveness. There was a significant difference between the groups (p<0.001) for microbial load, metabolic activity and biofilm viability. Conclusions: It was concluded that the BvK, Ec and Ps dentifrices are useful for cleaning complete dentures, as they have antimicrobial activity against biofilm. The dentifrices containing Bowdichia virgilioides Kunth showed medium abrasiveness and should be used with caution.